Analysis of UNWAHA Jombang Student's Perspectives in Learning Religion Through Social Media - Aufia Aisa; Endrik Ratnawati (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
This study aims to find out how effective learning religion through social media is according to UNWAHA students, how UNWAHA students use social media wisely, and the influence of social media on religious learning according to UNWAHA students. The approach used to achieve the above objectives is to use a qualitative research approach. In collecting data, the author uses the method of questionnaires, interviews, and documentation. The results show that learning religion through social media is quite effective because it makes it easier to find material, and tends not to be boring. They use social media wisely by sorting out good information and references, looking for sources from the information obtained, and not spreading information without the right sources. The impacts of learning religion through social media are positive impacts such as facilitating learning activities, and adding insight into religion. While the negative impact is causing addiction to social media which can reduce interest in reading books, sources of information that are not necessarily valid and regarding misuse in disseminating information.